2015
DOI: 10.1002/chem.201502752
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Bromide: An Alternative Emitter for Blue‐Colored Flame Pyrotechnics

Abstract: Copper(I) bromide was evaluated as an alternative emitter for blue flame pyrotechnic compositions. CuBr and CuCl emission spectra were recorded from a butane torch flame and compared. Cu(BrO3 )2 was synthesized and used in pyrotechnic compositions as an oxidizer and the source for the generation of CuBr species. Pyrotechnic compositions, which contained copper and potassium bromates as oxidizers, were optimized for the generation of blue flames. The experimental data, including emission spectra of the flames, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…More recent studies have since demonstrated that copper(I) bromide (CuBr) also serves as a blue-light-emitter [42]. In fact, this specie was found to impart the deepest hue of blue light of the blue-light emitters.…”
Section: Removal Of Heavy Metals From Pyrotechnic Illuminantsmentioning
confidence: 99%
“…More recent studies have since demonstrated that copper(I) bromide (CuBr) also serves as a blue-light-emitter [42]. In fact, this specie was found to impart the deepest hue of blue light of the blue-light emitters.…”
Section: Removal Of Heavy Metals From Pyrotechnic Illuminantsmentioning
confidence: 99%
“…Recent efforts have been made to identify alternatives to well-known copper-chlorine based systems. Some of us have published work on copper(I) bromide and compared it to copper(I) chloride [13]. The work includes the 1931 CIE coordinates for the isolated spectra of CuCl and CuBr.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work was done to deepen the understanding of the underlying phenomena during the 1950s to 1960s , though without affecting much of the products already in use. The main driving force in development in recent years has been focused on eliminating certain unwanted ingredients and to a certain degree improving flame color depth .…”
Section: Introductionmentioning
confidence: 99%